MASHLAHAH AL MURSALAH DALAM KONSEP KENEGARAAN MENURUT IMAM AL GHAZALI - Haniatunnisa, Siti (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2021)
Imam al Ghazali as Islamic Scholar expert in the field of ushul fiqh, His thoughts in the field of ushul serve as a reference throughout the world and also in Indonesia for centuries. He is also one of the scholar who uses Mashlahah al-mursalah approach results in ijtihad. He formulates in the methodology in his famous books include Al-Mustashfa, Syifa'ul Ghalil and al-Mankhul on the provisions of the use mashlahah al mursalah. In addition al Ghazali also formulated a concept of state. The concept of state formulated by al Ghazali stands on the basis of the theory of interdependency and the theory of theo-democracy. In the concept of statehood, we find that al Ghazali uses the principle of Mashlahah as the basis or reference in the built of state. Al Ghazali in the concept of theo-democracy using Mashlahah al Mursalah as the basis of law in order to build people's sovereign State by using the principles of divinity (Mabadi Rabbaniyah). The concept of theo-democracy, is a concept of a moderate state (tawashutiyyan), which is not in the form of God State (theocracy) or Secular state, but it is in the middle between that two models of the State, namely the State which remain within the corridor etiquette and principles of divinity yet at the same time provide a soverignity in technical life of a country to a nation. Keywords: Imam al-Ghazali,Islamic scholar, ushul fiqh